2021
DOI: 10.30870/jels.v6i2.11582
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Online Paraphrasing Tools to Overcome Students’ Paraphrasing Difficulties in Literature Reviews

Abstract: One of the prevalence of digital technology in academic writing, particularly in literature reviews, is the use of paraphrasing tools. However, there is a lack of research focusing on overcoming students' paraphrasing difficulties in writing. Using the notion of Schuemann, C., , this paper explores students' difficulties with paraphrasing and the use of online paraphrasing tools. A descriptive qualitative approach was used to collect data from 30 students enrolled in the Magister's of English Language Educatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 0 publications
4
8
0
1
Order By: Relevance
“…The use of Quillbot in the writing process, indeed, directs students to better and high-quality writing content (Syahnaz & Fithriani, 2023;Kurniati & Fithriani, 2022), so the above results confirmed the improvement in the quality of participants' writing, especially in the aspects of vocabulary and grammar. A similar result is also shown in previous research conducted by Sulistyaningrum (2021) where in that study, an average of 3.67 out of 30 students mentioned that Quillbot helped them in applying correct grammar and finding the right synonyms. Quillbot's ability to paraphrase sentences by switching the wording or providing synonyms to the user was also considered by participants to improve the quality of their writing, considering that they will produce writing using a more sophisticated vocabulary, not seem too monotonous, and look more academic.…”
Section: Resultssupporting
confidence: 88%
“…The use of Quillbot in the writing process, indeed, directs students to better and high-quality writing content (Syahnaz & Fithriani, 2023;Kurniati & Fithriani, 2022), so the above results confirmed the improvement in the quality of participants' writing, especially in the aspects of vocabulary and grammar. A similar result is also shown in previous research conducted by Sulistyaningrum (2021) where in that study, an average of 3.67 out of 30 students mentioned that Quillbot helped them in applying correct grammar and finding the right synonyms. Quillbot's ability to paraphrase sentences by switching the wording or providing synonyms to the user was also considered by participants to improve the quality of their writing, considering that they will produce writing using a more sophisticated vocabulary, not seem too monotonous, and look more academic.…”
Section: Resultssupporting
confidence: 88%
“…The significant distinction between the pre-test and post-test indicated that the SMS application supplementary has been effective in paraphrasing sentences (Arani, 2016). The digital paraphrase was designed to change the matching words through software and never intended to duplicate human language (Sulistyaningrum, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Sulistyaningrum's [34] study on students' attitudes and perceptions of social media technology revealed that, while most students are aware of its potential for educational purposes, concerns about rules and regulations, as well as the inability to control it, were raised. In a follow-up study, Chen et al [35] developed a corpus-based paraphrasing tool to assist EFL students in improving their writing skills.…”
Section: Literature Reviewmentioning
confidence: 99%